Postoperative anion gap associates with short- and long-term mortality after cardiac surgery: A large-scale cohort study - Li, Jiajing; Tian, Yu; Wang, Lingzhi; Chen, Jiayue; Chen, Xiaoshu; Huang, Huansen; Li, Yihao (Frontiers in Cardiovascular Medicine, 2022)
Objective To investigate whether postoperative anion gap (AG) is associated with short- and long-term mortality in patients following cardiac surgery. Materials and methods We conducted a retrospective cohort study of adults who underwent cardiac surgery from the Medical Information Mart for Intensive Care - III database. The generalized additive model (GAM), logistic regression, and Cox regression were performed to assess the correlations between AG levels and in-hospital, 90-day, and 4-year mortality. Linear regression was used to evaluate the associations between AG and length of stay (LOS). Results Totally, 6,410 subjects were enrolled in this study and classified into tertiles based on the initial AG levels. The GAM indicated a positive association between initial AG and in-hospital mortality after adjusting for potential confounders. Multivariate logistic analysis revealed that the risk of in-hospital mortality was higher among patients in tertile 2 (OR 2.05, 95% CI 1.11–3.76, P = 0.021) and tertile 3 (OR 4.51, 95% CI 2.57–7.91, P < 0.001) compared with those in tertile 1. For 90-day and 4-year mortality, multivariate Cox regression found similar associations between AG tertiles and mortality. The LOS in ICU and hospital also increased as AG tertiles increased. The E-value indicated robustness to unmeasured confounders. Conclusion This study found a positive association between postoperative AG levels and short- and long-term mortality among patients after cardiac surgery. This relationship warrants further research.